Karakterisasi Sebaran Binomial Negatif-Eksponesial - Handayani, Deby (UIN Imam Bonjol Padang, 2021)
This study discusses the convolution or the sum of independent and identical random variables, where the random variables are the Negative Binomial distribution and the Exponential distribution, so that the resulting distribution is known as the Negative Binomial -Exponential distribution. The purpose of this study is to find the characteristics of the distribution including the expected value, the variance value, the moment generating function and the characteristic function. This property is obtained by using theorems and lemmas that relate to the properties of a distribution. It is found that the expected value, variance value, moment generating function and characteristic function of the Negative Binomial-Exponential distribution.